Counseling on making dragon fruit skin ginger powder drink 'JAKUNA' - Sinta Ratna Dewi; Siti Juliana Putri; Iga Mawarni; Evi Yanti; Alda Adelia (Universitas Muhammadiyah Magelang, 2024)
Dragon fruit skin ginger powder drink is a nutritious beverage that combines the health benefits of ginger and dragon fruit. This blend results in a drink packed with antioxidants, vitamins, and other essential nutrients. Ginger is renowned for its anti-inflammatory properties and immune-boosting effects, while dragon fruit is rich in vitamin C, fiber, and antioxidant compounds. The objective of this initiative is to promote the utilization of red ginger and dragon fruit peel in creating processed healthy beverages. It aims to enhance community knowledge and skills in transforming ginger and dragon fruit peel into nutritious drinks, as well as to create entrepreneurial opportunities within the community. The approach involves providing counseling sessions. As a result of this activity, there has been an emergence of ideas and motivation in producing JAKUNA instant powder drinks, following increased training subsequent to counseling on the production of such beverages.